The silver crown - O'Brien, Robert C. (New York : Aladdin Paperbacks, 2001)
Ellen awakens on her tenth birthday to find a jewel- studded silver crown, loses her family and home in a fire later that day, and plunges into a series of dangerous adventures that test her courage, ingenuity, and independence of spirit.
Originally published: New York : Atheneum, 1968.
Keywords: Fantasy